Rancang Bangun Alat Pengaduk Adonan Mie dan Kulit Pangsit Melalui Pendekatan Atropometri Guna Meningkatkan Efisiensi Waktu Kerja (Studi Kasus: UMKM Mie Karanganyar) - Rizal Hakim; Jaka Purnama (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Mie Karanganyar MSME is a business engaged in the production of noodles and wonton wrappers, where the dough mixing process is still carried out manually. This process requires approximately 34.5 minutes to mix 30 kg of dough, often resulting in production delays, employee overtime, and reduced work productivity.This study aims to design an ergonomic dough mixer for noodle and wonton wrapper production using an anthropometric approach to improve production efficiency. The anthropometric measurements used include standing elbow height, shoulder width, waist height, and forward reach as the basis for determining the machine dimensions. The design resulted in a machine with a height of 96.2 cm, a length of 133.21 cm, and a width of 65.6 cm, which are compatible with the operator’s body dimensions, thereby improving comfort and safety during operation. The manufacturing cost of the machine was Rp. 6,015,000. The implementation of the dough mixer significantly reduced the mixing time from 34.5 minutes to 15.7 minutes. The machine also increased production capacity, reduced the need for overtime work, and lowered production costs from Rp. 6,015,000 to Rp3,208,664, resulting in a cost saving of Rp. 2,806,336. Therefore, the proposed machine can improve work efficiency, productivity, and the competitiveness of Mie Karanganyar MSME.